PENENTUAN UMUR SIMPAN KRIPIK PISANG KEJU GORONTALO DENGAN PENDEKATAN KURVA SORPSI ISOTERMIS.[Self-life Determination of Gorontalo Chesee Banana Chips Approach to Curve Sorption Isotherm Curve] - Maku, Merywati; Mamuaja, Christine F.; Tooy, Dedie (Jurnal Ilmu dan Teknologi Pangan, 2014)
Gorontalo cheese banana chips is one of the products of small and medium enterprises that are integrated agro industrial region that has not been included on the packaging, shelf life so that consumers do not know the shelf life of the product. Research carried out by determining the initial moisture content and the determination of the critical water content with organoleptic test. To determine the sorption isotherm curve used five types of salt is NaOH, MgCl2, NaBr, NaCl and BaCl2, and observed every day. Determination of the critical moisture content, equilibrium moisture content, models and sorption isotherm curve, slope, permeability of packaging, weight and packaging for a wide shelf life calculation Labuza on acceleration method to approach the critical moisture content. Total mold testing done to determine how much contamination of mold on cheese samples of banana chips. From this study it can be concluded self-life of cheese banana chips based approach sorption isotherm curve is 116.37 days or 3.88 months. Cheese banana chips which are in critical condition does not contain mold.